Unitarian Universalist Church of Fresno Secret Friends Sunday - Watkins, Howard::::::::: (1988)
Close up of Secret Friends: Norelma Walker and ?, Bette Peterson and ?, ?and Adam Watkins John Freeman and Bob Jones wearing hat on far right